CatDog Season 4, The final season [videorecording (DVD)] - Cummings, Jim, 1952-; Kenny, Tom, 1962- (CatDog (Television program), 2013)
A brand new set of insane adventures! They're the craziest set of conjoined twins you'll ever meet: the culturally refined Cat, and Dog, who's, well, not so much! But together, CatDog make it all work by both using and strengthening their own friendship, providing their own excitement, and even getting into their own heap of hilarious trouble!